Tari sebagai Kegiatan untuk Meringankan Trauma pada Anak Korban Kekerasan Seksual - Sarajar, Michelle; Yetti, Elindra; Haerudin, Deden (Program Studi Pendidikan Tari FBS UNJ, 2023)
With numerous productive ages in Indonesia, gold in Indonesia 2024 is anticipated. However, from 2019 through 2022, there has been an upsurge in child sexual abuse. Due to the alarming rise in cases, the study has been done to examine the literature's findings on the topic of using dance activities to lessen the trauma experienced by young victims of sexual abuse. This study intends to assess the literature on the use of dance activities to lessen the trauma experienced by young victims of sexual abuse. This research was conducted with a qualitative research method using types of literature. Scientific publications, electronic books, and non-electronics are used in research to examine the design of dancing exercises for child sexual abuse victims and their effects on easing their trauma. The analysis of this study's findings revealed that children can express themselves nonverbally through dance activities like dance/movement therapy and creative art therapy, which give them the freedom to move. Children can also express their emotions nonverbally by experimenting with movement and their imagination. As a result of these activities, participants experience increased self-assurance, emotional understanding and expression, self-connection, social skills, and trust in their parents or other caregivers. This study has the potential to be used to study contemporary dance and other forms of dance.